Data-driven research on vehicles' risky lane-changing manoeuvre - Chen, Tianyi (Nanyang Technological University, 2021)
Risky Lane-changing (LC) manoeuvre can lead to serious damage to property and great loss of life. Hence, it is of great significance to investigate into risky LC manoeuvre and improve road traffic safety. However, the research on risky LC manoeuvre faces the challenges of rare crash data, behavioural complexity, multiple contributing factors, and sophisticated causal mechanism. This research is undertaken to resolve various challenges in four phases (i.e., Phases 1 to 4), which are briefly summarised as below. Next Generation Simulation (NGSIM) dataset is used to validate the studies in Phases 1 to 3, while in Phase 4 the Second Highway Research Program (SHRP2) Naturalistic Driving Study (NDS) dataset is applied for method validation.